2009
DOI: 10.1029/2008ja013982
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of narrowband emission observed in the Saturn magnetosphere

Abstract: [1] Narrowband emission is observed at Saturn centered near 5 kHz and 20 kHz and harmonics of 20 kHz. This emission appears to be in many ways similar to Jovian narrowband emission observed at higher frequencies. We analyze one example of this emission near a possible source region. In situ electron distributions suggest narrowband emission has a source region associated with electrostatic cyclotron harmonic and upper hybrid emission. Linear growth rate calculations indicate that the observed plasma distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…We have been fortunate to obtain electron phase space densities with a sufficient pitch angle distribution for analysis. The results reported here support and extend the work of Menietti et al (2009).…”
Section: Discussion and Summarysupporting
confidence: 80%
See 3 more Smart Citations
“…We have been fortunate to obtain electron phase space densities with a sufficient pitch angle distribution for analysis. The results reported here support and extend the work of Menietti et al (2009).…”
Section: Discussion and Summarysupporting
confidence: 80%
“…Ye et al (2009) In this paper we examine in some detail new examples of NB observed by Cassini at Saturn with center frequency near 15 kHz. The examples are associated with electrostatic cyclotron harmonic (ECH) emission and probable upper hybrid waves, similar to the case examined by Menietti et al (2009), but in this new case, the source is in the Northern Hemisphere and the ratio of f p /f ce appears to be somewhat higher. We conduct a similar analysis of the in-situ wave and particle data, including a spatial growth calculation, to demonstrate that the cyclotron maser instability is likely responsible for the direct generation of Z-mode emission which may mode convert to O mode or NB emission as observed.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Ye et al [2010b] showed that the L-O mode narrowband emissions are mode converted from Z mode narrowband emissions observed near Saturn. Less intense narrowband emissions at higher frequencies (∼ 10-70 kHz) are found to originate from upper hybrid resonance emissions on the boundary of the plasma torus Menietti et al, 2009;. A review of the studies on Saturn narrowband emissions can be found in Ye et al [2011].…”
Section: Narrowband Emissionmentioning
confidence: 99%